A randomized control trial of the effect of yoga on verbal aggressiveness in normal healthy volunteers - Deshpande, Sudheer (Medknow Publications, 2008)
OBJECTIVE: To study the effect of yoga on verbal aggressiveness in normal healthy adults. METHODS: Of the 1228 persons who attended introductory lectures, 226 subjects of both sexes who satisfied the inclusion and exclusion criteria and who consented to participate in the study were randomly allocated into two groups. These 226 subjects were between the ages of 17 and 62 years and 173/226 completed the eight weeks of intervention. The Yoga (Y) group practised an integrated yoga module that included asanas, pranayama, meditation, notional correction, and devotional sessions. The control group practised mild to moderate physical exercises (PE). Both groups had supervised practices (by trained experts) for one hour daily, six days a week for eight weeks. Verbal Aggressiveness was assessed before and after eight weeks using the self-administered Verbal Aggressive Scale. RESULTS: The baseline score of the two groups did not differ significantly (P = 0.66). There was a significant decrease in verbal aggressiveness in the yoga group (P = 0.01 paired samples t-test) with a nonsignificant increase in the PE group. ANCOVA using pre- values as covariates showed a significant difference between the groups (P = 0.013). RMANOVA for interaction between the sexes or age groups in change scores were not significant. CONCLUSIONS: This study has demonstrated that an eight week intervention of an integrated yoga module decreased verbal aggressiveness in the yoga group (in males and those below 25 years of age), with a nonsignificant increase in the PE group.